Analysis of Factors Influencing Refusal of Women of Childbearing Age to Undergo Visual Inspection with Acetic Acid in Beringin Jaya Village, Oba Tengah District - Nurrizchawaty S; Widia Shofa Ilmiah (Lembaga Pengembangan Kinerja Dosen, 2025)
Refusal of Visual Inspection with Acetic Acid (VIA) examination remains a major challenge in cervical cancer early detection, particularly among women of reproductive age. This study aimed to analyze factors influencing refusal of VIA examination among women of reproductive age in Beringin Jaya Village, Oba Tengah District. A quantitative analytic study with a cross-sectional design was conducted involving 74 respondents. Data were collected using a structured questionnaire assessing educational level, knowledge, information, and the role of health workers. Data analysis included univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using ordinal logistic regression.The results showed that most respondents refused or hesitated to undergo VIA examination. Bivariate analysis demonstrated that educational level, information, and the role of health workers were associated with refusal of VIA examination, while knowledge level showed a tendency toward association. However, multivariate analysis revealed that only the role of health workers had a statistically significant effect on refusal of VIA examination. Educational level, knowledge, and information were not significant predictors after adjustment.These findings indicate that service-related factors, particularly the role of health workers, are more influential than individual factors in shaping decisions regarding VIA examination. Strengthening health workers’ roles through effective communication and interpersonal counseling is essential to improve VIA examination uptake.